Pengaruh Persepsi Layanan Jemput Zakat Terhadap Kepuasan Muzakki Di Lembaga Amil Zakat Yatim Mandiri Cabang Jombang - Erliana, Nelly; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2018)
Thuse number of Amil Zakat Institution caused of competition among them, so there should be service improvement through pick up zakat. This study aims to determine the impact of the service perception of pick up zakat to muzakki satisfaction in Amil Zakat Institution Yatim Mandiri Jombang Branch. This study uses quantitative approach associative with data through questionnaire. The result of hypothesis test shows that the service perception of pick up zakat has a significant effect on the satisfaction of muzakki.